Functional Tricuspid Regurgitation: Behind the Scenes of a Long-Time Neglected Disease - Vinciguerra, Mattia; Sitges, Marta; Luis Pomar, Jose; Romiti, Silvia; Domenech-Ximenos, Blanca; D'Abramo, Mizar; Wretschko, Eleonora; Miraldi, Fabio; Greco, Ernesto (Frontiers in Cardiovascular Medicine, 2022)
Severe tricuspid valve regurgitation has been for a long time a neglected valve disease, which has only recently attracted an increasing interest due to the notable negative impact on the prognosis of patients with cardiovascular disease. It is estimated that around 90% of tricuspid regurgitation is diagnosed as “functional” and mostly secondary to a primary left-sided heart disease and, therefore, has been usually interpreted as a benign condition that did not require a surgical management. Nevertheless, the persistence of severe tricuspid regurgitation after left-sided surgical correction of a valve disease, particularly mitral valve surgery, has been associated to adverse outcomes, worsening of the quality of life, and a significant increase in mortality rate. Similar results have been found when the impact of isolated severe tricuspid regurgitation has been studied. Current knowledge is shifting the “functional” categorization toward a more complex and detailed pathophysiological classification, identifying various phenotypes with completely different etiology, natural history and, potentially, an invasive management. The aim of this review is to offer a comprehensive guide for clinicians and surgeons with a systematic description of “functional” tricuspid regurgitation subtypes, an analysis centered on the effectiveness of existing surgical techniques and a focus on the emergent percutaneous procedures. This latter may be an attractive alternative to a standard surgical approach in patients with high-operative risk or isolated tricuspid regurgitation.